Single-step exfoliation and chemical functionalisation of graphene and hBN nanosheets with nickel phthalocyanine - NICOLOSI, VALERIA (My University, 2012)
Versatile routes to functionalise few-layer graphene and hBN with nickel phthalocyanine (Ni-Pc) were achieved using liquid phase exfoliation and sonication methods. EDX performed on the graphene//Ni-Pc specimen showed nickel on the flake surface whilst Raman spectroscopy revealed a prominent D peak indicating the presence of basal plane defects. New Raman active modes were also found in the hBN//Ni-Pc complex. X-ray photoelectron spectroscopy showed a charge transfer for both graphene and hBN confirming that the flake edges and basal-planes were covalently functionalised by the phthalocyanine molecules. Transmission electron microscopy confirmed the only presence of single and few-layer flakes of hBN and graphene in solution, demonstrating that the exfoliation yield was not affected by the functionalisation step. We therefore proved that tuning of the electronic and optical properties of graphene and hBN nanosheets is indeed conceivable. We used the Z-scan technique to prove the nonlinear optical (NLO) behaviour of the functionalised graphene sheets. Based on such optical response, we demonstrate an optical limiting effect for nanosecond laser pulses at 532 nm, proving these materials to be a suitable candidate for photonic and optoelectronic applications
PUBLISHED
Keywords: graphene